Filsafat Matematika dan Ragam Teka Teki Klasiknya - Novianti, Dwi Erna; Rochmad; Isnarto (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2022)
This study aims to describe classical puzzles in the philosophy of mathematics. This research is a type of Systematic Literature Research (SLR) that uses several reference sources, especially on the philosophy of mathematics. Philosophy is one of the things that underlies a science, there is no development of mathematics. There are so many philosophers who have developed mathematics for a long time, such as Plato, Frage and Pythagoras. Philosophy and mathematics itself is an important part that can not be separated. In general, the philosophy of mathematics is basically an experiment in compiling a collection of mathematical knowledge that is disorganized over centuries and is given certain symbols and symbols. Meanwhile, there are classic puzzles in the philosophy of mathematics that discuss mathematics from several points of view. Among them are: 1) is mathematics created or discovered, 2) is mathematics finite or infinite, and 3) is mathematics process or object. Based on the results of a review of several references, it is described that each of these puzzles has its own role in the development of mathematics.